How Do Countries Choose their Exchange Rate Regime? - Poirson, Helene (IMF Working Papers; Working Paper ;, 2001)
This paper investigates the determinants of exchange rate regime choice in 93 countries during 1990-98. Cross-country analysis of variations in international reserves and nominal exchange rates shows that (i) truly fixed pegs and independent floats differ significantly from other regimes and (ii) significant discrepancies exist between de jure and de facto flexibility. Regression results highlight the influence of political factors (political instability and government temptation to inflate), adequacy of reserves, dollarization (currency substitution), exchange rate risk exposure, and some traditional optimal currency area criteria, in particular capital mobility, on exchange rate regime selection.